Sensory Tricks Are Associated with Higher Sleep-Related Quality of Life in Cervical Dystonia. (17th June 2019) - Benadof, Casey N.; Cisneros, Elizabeth; Appelbaum, Mark I.; Stebbins, Glenn T.; Comella, Cynthia L.; Peterson, David A.
Background: Sensory tricks are compensatory gestures that cervical dystonia (CD) patients use to reduce abnormal neck posture and movements. Although sensory tricks are common in CD, little is known about whether trick efficacy changes over time or has effect on quality of life. Methods: We analyzed clinical data and video recordings from 188 patients with isolated CD. We calculated the duration of CD and assessed the Toronto Western Spasmodic Torticollis Rating Scales and the Cervical Dystonia Impact Profile (CDIP-58). Results: A longer duration of CD corresponded to a less effective sensory trick (r(187) = 0.1901, p = 0.009). Patients who demonstrated more effective sensory tricks reported higher sleep-related quality of life than patients with less effective sensory tricks (r(187) = 0.1680, p = 0.0212). There were no significant relationships between the effectiveness of a sensory trick and the other aspects of quality of life as measured by the CDIP-58. Discussion: Patients who have had CD longer had less effective sensory tricks consistent with patients' verbal reports of previously having a trick that no longer works. Patients should be apprised of a wide variety of sensory tricks because their previous tricks may lose efficacy over time and because more effective tricks are associated with higher sleep-related quality of life.